Third-party logistics providers in the digital age: Towards a new competitive arena? - Erik Hofmann; Florin Osterwalder (Logistics, 2017)
This paper looks at the impact of digitalization on third-party logistics (3PL) business models. An eclectic framework for the analysis of digital disruptions in service industries is elaborated by linking Porter's five forces to insights from research on digitalization and innovation. Applying this framework to the business field of 3PL reveals that logistics service providers face significant digital hardship from new technologies such as autonomous vehicles and 3D printing as well as from platform-based business models and the sharing economy. We see the following changes in the competitive arena: First, 3PLs focusing on standard services may lose significant market share in the near future. Second, management-related 3PL activities seem to be increasingly offered by new external competitors, which may downgrade 3PLs to simple forwarders. Third, digitalization enables the forward or backward integration of 3PL customers and suppliers when they establish their own services. In addition to its threats, the opportunities of digitalization for 3PLs are discussed. These include the customization of standardized logistics services, the provision of cloud logistics services, platform-based asset and logistics infrastructure sharing, the 'physical internet' as a future transportation system and the adoption and integration of 3D printing into existing 3PL business models.
Keywords: 650; digital disruptions; digitization; e-business; industrial economics; logistics; third-party logistics (3PL)